2011
DOI: 10.1159/000326908
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Mild General Paresis of the Insane: AD-Like Pattern

Abstract: Background/Aims: We investigated the clinical and cognitive features of patients with mild general paresis of the insane (GPI) in comparison to Alzheimer’s disease (AD) patients, mild frontotemporal dementia (FTD) patients and normal elderly individuals. Methods: Twelve patients with mild GPI, 24 patients with mild AD, 11 patients with mild FTD and 36 healthy subjects participated in the current study. A comprehensive neuropsychological battery was used to assess memory, language, attention, executive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
7
26
0
1
Order By: Relevance
“…A comprehensive neuropsychological battery was used, which included assessments of memory, language, attention, executive function and visuospatial ability. All tests have been shown to have good reliability and validity when used in Chinese populations [10]. The specific tests employed were: the Center for Epidemiologic Studies Depression Scale [11]; the Auditory Verbal Learning Test (AVLT) [12], [13]; the Rey-Osterrieth Complex Figure Test (CFT) [13], the event-based prospective memory test (EBPM) and the time-based prospective memory test (TBPM) [14], [15]; the Boston Naming Test (BNT, 30-item version) [16]; the verbal fluency test (VFT) [17]–[19]; the Trail Making Test, parts A and B (TMT-A, TMT-B) [20]; the Symbol Digit Modalities Test (SDMT) [21]; the Stroop Color-Word Test (SCWT) [22]; the similarity test [23]; the stick test [24]; and the clock drawing test (CDT) [25], [26].…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive neuropsychological battery was used, which included assessments of memory, language, attention, executive function and visuospatial ability. All tests have been shown to have good reliability and validity when used in Chinese populations [10]. The specific tests employed were: the Center for Epidemiologic Studies Depression Scale [11]; the Auditory Verbal Learning Test (AVLT) [12], [13]; the Rey-Osterrieth Complex Figure Test (CFT) [13], the event-based prospective memory test (EBPM) and the time-based prospective memory test (TBPM) [14], [15]; the Boston Naming Test (BNT, 30-item version) [16]; the verbal fluency test (VFT) [17]–[19]; the Trail Making Test, parts A and B (TMT-A, TMT-B) [20]; the Symbol Digit Modalities Test (SDMT) [21]; the Stroop Color-Word Test (SCWT) [22]; the similarity test [23]; the stick test [24]; and the clock drawing test (CDT) [25], [26].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to AD and DLB, general paresis (GP), a chronic meningoencephalitis caused by direct invasion of the brain parenchyma by spirochetes, is also associated with amyloid deposits [17]. Patients with GP usually present with atrophy of the medial temporal lobe and AD-like cognitive impairment [18]. Inflammation and neurodegeneration can be found in the cortex of patients with GP [19].…”
Section: Introductionmentioning
confidence: 99%
“…CSF levels of Aβ (1-42), which are believed to represent amyloid plaque pathology, were decreased in the atrophic form of general paresis [12,22]. Although neurosyphilis encompasses AD-like cognitive impairment [11] and AD-like decreases in CSF Aβ (1-42) [12], we found discrepancies in neuropsychiatric syndromes between neurosyphilis and AD. In patients with AD, the score on the psychosis and psychomotor syndrome factor increased significantly with disease severity across the spectrum of MCI, mild dementia, and severe dementia.…”
Section: Discussionmentioning
confidence: 92%
“…Some clinical features of patients with neurosyphilis have been described as similar to those seen in patients with AD. Wang et al [11] showed a similar pattern of cognitive impairments in memory, language, and executive function between patients with neurosyphilis-dementia and patients with mild AD. Biologically, patients with AD and those with neurosyphilis-dementia appear to share decreased Aβ42 in the cerebral spinal fluid (CSF) [12].…”
Section: Introductionmentioning
confidence: 96%